Kecerdasan Emosi Dalam Kempemimpinan Kristen di Abad 21 - Krido Siswanto; Ayu Rotama Silitonga (Sekolah Tinggi Teologi ATI Anjungan Pontianak, 2021)
Christian leadership is leadership that is able to encourage and move the people being led to carry out activities that have been designed. In the 21st century, many changes have occurred. As a Christian leader, you must be able to follow developments and answer every problem experienced by the people you lead. In leading, it is necessary to have a skill, namely to have a heart that is willing to serve like Jesus. In this case, emotional intelligence is needed in Christian leadership to control and understand the feelings that are actually being experienced, so that leaders are able to make wise decisions. The question is what are the importance of emotional intelligence in Christian leadership? This paper aims to understand and understand some of the importance of emotional intelligence in Christian leadership. The method used is the Literature method by observing books and journals to support writing.